Axial Backmixing and Residence Time Distribution in a Miniaturized, Stirred‐Pulsed Extraction Column. Issue 1 (7th December 2017) - Soboll, Sebastian; Bittorf, Lukas; Kockmann, Norbert
Abstract: Axial backmixing is an important issue in extraction columns since it heavily affects the mass transfer performance. A miniaturized, stirred‐pulsed column was investigated regarding its backmixing characteristics in the continuous phase, using the system water/ n ‐butyl acetate. Residence time distributions were determined through pulse experiments with potassium chloride, which was detected via electrical conductivity. To perform the conductivity measurement without distortion of the two‐phase flow, electrodes with an annular design that precisely line up with the inner column wall were manufactured. This design is a promising alternative for use in small‐scale tubular devices where commercial electrodes do not fit and in applications where interference with the flow must be avoided. Abstract : Miniaturized extraction columns are a useful tool for process development as they allow simple and fast investigations of countercurrent extraction processes on the laboratory scale, e.g., for feasibility studies. Additionally, preliminary data for column scale‐up can be gathered with less effort than in pilot‐scale columns.